DEAFNESS, EDUCATION AND HEALTH: a systematic review of theses and dissertations produced between 1987 and 2020 - Meira, Fernanda Meira (2024)
This paper aimed to identify academic productions on deafness carried out in broad knowledge areas within the Human Sciences and Health Sciences scope, correlating deafness-education and deafness-health. This is a systematic analysis performed from the microdata available on the Portal Brasileiro de Dados Abertos no Catálogo de Teses e Dissertações da CAPES (Brazilian Open Data Portal in the CAPES Dissertations and Theses Catalog, 1987-2020), using as reference the keywords deafness, deaf, hearing impaired and hearing impairment. The search made it feasible to locate 1,843 studies. After applying the inclusion criteria as for broad knowledge area, title, and keywords, 1,675 dissertations and theses were selected and analyzed in two stages. The first stage comprised information regarding the variables: year of publication, region, state, broad knowledge area, knowledge area, gender of the author, and level of production (thesis or dissertation). The second stageconsisted of analyzing the textual data of the keywords by using the Iramuteq software through Confirmatory Factor Analysis (CFA), Descending Hierarchical Classification (CHD), Similitude, and word cloud. The results evince an increase of studies in the area of deafness aimed at the growth of research in Human Sciences, an ongoing process since 1990. It was also possible to observe that research in Health Sciences is more strongly correlated with the clinical aspects of deafness, which has undergone changes due to the increase in research related to linguistic and social issues in Speech-Language Pathology. In HumanSciences research, studies related to the socio-anthropological perspective of deafness predominate by focusing on sign language, deaf culture, and deaf identity.